Outcome of unplanned right ventricular assist device support for severe right heart failure after implantable left ventricular assist device insertion - Takeda, Koji; Naka, Yoshifumi; Yang, Jonathan A; Uriel, Nir; Colombo, Paolo C; Jorde, Ulrich P; Takayama, Hiroo (The Journal of heart and lung transplantation, 2014)
The use of a right ventricular assist device (RVAD) becomes necessary for severe right ventricular (RV) failure after left ventricular assist device (LVAD) insertion. Although temporary support could lead to successful RVAD weaning in certain patients, the data remain scarce. We retrospectively reviewed 398 patients who underwent implantable LVAD insertion between January 2000 and December 2012. Of these patients, 44 (11%) required unplanned RVAD support due to severe RV failure after LVAD insertion. For comparison, 37 patients who underwent planned biventricular assist device (BiVAD) insertion were identified during the same study period. We analyzed the early and late outcomes in these patients. The mean duration of RVAD support was 21 ± 23 days. Of the 44 patients, 21 (49%) were weaned from the RVAD (weaning group), whereas 23 (51%) required continued biventricular support (failure group). The failure group had ongoing end-organ dysfunction after RVAD insertion. Hospital mortality was significantly lower in the weaning group (24%) and in the planned BiVAD group (30%) as compared to the failure group (74%, p = 0.0009). The 6-month actuarial survival rate was 75% in the weaning group, 62% in the planned BiVAD group and 13% in the failure group (p < 0.0001). Successful bridge to transplant was achieved in 14 patients (67%) in the weaning group as compared with 8 patients (35%) in the failure group (p = 0.03). On multivariate logistic regression analyses, pre-operative white blood cell (odds ratio [OR] 1.3, 95% confidence interval [CI] 1.04 to 1.50, p = 0.016) and creatinine (OR 0.26, 95% CI 0.079 to 0.88, p = 0.03) levels were significant predictors for RVAD removal. Among patients who developed acute RV failure after LVAD insertion, only half could be weaned from the temporary RVAD support. An alternative strategy is necessary in patients who require continuous RVAD support.